Evaluating the Curriculum of General Methods of Teaching in the Institutes of Fine Arts according to the Students Perspective - Gazi. Dawod, Lect . Sabah (Basra studies journal, 2025)
The current study aimed at evaluating the curriculum of the courses of curriculum designs and general teaching methods in the Institutes of Fine Arts from the students perspective. The researcher adopted a descriptive research method to achieve the objective of the study. The researcher developed a research tool (i. e. a questionnaire) consisting of 30 items distributed across six domains : objectives، content, teaching methods، educational tools، educational activities، and assessment. After verifying the validity and reliability of the research tool، it was administered to a sample of second year students from the Institutes of Fine Arts in Basra Governorat, totaling 193 male and female students. The researcher used pearsons correlation coefficient , weighted mean، and percentage weight as appropriate statistical methods for the research procedures. Several Finding related to the evaluation of the General Teaching Methods subject curriculum were reached. The researcher presented and interpreted the results, and based on the finding of the study, Several conclusions، recommendations، and Suggestions were made.